Characterization of the cultured human keratinocytes - Hoà, Trần Lê Bảo (Vietnam Journal of Biotechnology, 2011)
Epidermis accounts for 90% of keratinocytes. The layer of keratinocytes that is closest to the basement membrane is called basal. It contains a number of proliferating cells. These cells are epidermal stem cells and transient amplifying cells. When cultured in vitro, keratinocytes are able to maintain proliferating, stemming, colonizing abilities. There are three types of colonies formed in vitro: (i) holoclone consists of cells with the highest proliferative capacity; (ii) paraclone consists of nearly differentiated cells; (iii) meroclone possesses of a wide range variety of cells that are different in proliferative capacity. The merolone is the transient phase between holoclone and paraclone. In this research, characteristics of the cultured human keratinocytes were evaluated. The human keratinocytes were isolated and cultured in SFM (Seram Free Medium). Markers of human keratinocytes were identified by RT-PCR. Proliferating and colonizing abilities of these cells were evaluated. Results showed that the cultured cells proliferated (up to double number in 24 hours). They also formed colonies and expressed the specific markers of keratinocytes such as p63, k5, kl4, involuerin.